Time Study as a Basis to Develop Strategies Aimed at Increasing the Efficiency of the Whipping Process of an Ice Cream Production Plant - Alfaro Pacheco, André Gianfranco (2020)
The subject of this research is the whipping process of an ice cream production plant of Delihelados, a company located in Bogotá, Colombia, where an inadequate distribution of personnel is observed on the production lines. Whipping times of the ice cream flavors and product offerings that represent 80% of sales, which are Cubetas retornables (returnable buckets, CR), Cubetas transparentes Perú (Peru transparent buckets, CTP) and Litro (liter, L), were analyzed in order to identify bottlenecks and develop strategies to reduce production times. The population analyzed was the internal client represented by 13 morning-shift operators. Results show that the bottleneck activity is filling, which depends on line efficiency (63%, 64% and 63%) and number of operators (3, 3 and 4) for CR, CTP and L vanilla product offerings. Furthermore, it was determined that balancing the production lines of the studied product offerings would potentially improve its efficiency and use of resources.